Gestión del control de inventario en la empresa Tuberías, Conexiones y Válvulas – Ecuador de la ciudad de Guayaquil - Bustamante Franco, María Mercedes (2019)
The company TUCOVA S.A, Pipes, Connections and Valves. It is dedicated to the importation, commercialization and distribution of: steel tubes, plastic and related tubes. This research was conducted in order to analyze and obtain a compression of this case study called Management Inventory Control Company. Maintaining good inventory management depends on the efficient management of stocks in warehouses, which is why some companies maintain merchandise, to meet and balance demand or inconvenience with production. Among the difficulties encountered within the company, is that financial management is deficient, in that the company does not maintain an order to keep track of the inventory